A review on Phytochemical and Pharmacological studies of Kundur (Boswellia serrata Roxb ex Colebr.) -A Unani drug - Mahe Alam, Hakimuddin Khan, L. Samiullah, K.M. Siddique (Journal of Applied Pharmaceutical Science)
Oleo-gum resin of Boswellia serrata Roxb ex Colebr. (Burseraceae) called Kundur in Unani system of Medicine is a prime ingredient in modern quality perfumes. The gum is popularly used in Indian Systems of Medicine (Unani, Ayurvedic & Sidha) for the last several centuries in curing various aliment especially rheumatism and skin diseases. Kundur is one of the popular drugs for various ailments such as dysentery, dyspepsia, lung diseases, haemorrhoids, rheumatism, urinary disorders and corneal ulcer in Unani system of medicine for the last several years. It is also an ingredient in certain compound formulations viz: Majoon Kundur, MajoonMurawwah-ul-Arwah, Dawa-ul-Kibrit and Habbe Suzak of Unani medicine used in renal disorders. The studies carried out on Kundur (Boswellia serrata Roxb) reveal that Oleo-gum resin exhibits potent Anti-fungal, Anti-complementary, Juvenomimetic and Anti-carcinogenic properties. Investigations on Kundur also revealed its beneficial effects in Immunomodulation, Bronchial asthma, Polyarthritis, Hepatitis C-virus, Colitis and Crohn's disease. Phytochemistry and pharmacology on Kundur (Oleo-gum resin) of Boswellia serrata Roxb has been reviewed in this paper with the view to justify its recorded uses in Unani System of Medicine on scientific lines.
Keywords: Kundur,Boswellia serrata,Unani drug,Phytochemistry.